Строение коренных зубов у Rhombomys opimus с заметками по систематике группы Rhombomys—Pliorhombomys (Rodentia, Gerbillinae) - Павлинов, И.Я. (Вестник зоологии, 1982)
A sample of a gerbil, Rhombomysoptimus, with rooted chick teeth has been col- lected in ran. it seems to be conspecific with gerbils of Middle Asia The genus Pliorhombomys is included to Rhomdomus. Dentition characteristics of Turan Central Asian populations of P. optimus is supposed T O phylogenetically "voung". so that distinctive status or the monotypic group Rhombomynae Hept. appears to be doubtful.